PENGARUH LAMA WAKTU FERMENTASI KOMBUCHA ROSELA (Hibiscus sabdariffa L.) TERHADAP AKTIVITAS ANTIBAKTERI Escherichia coli - Cholidah, Adinda Ismu; Danu, Dwi; Nurrosyidah, Iif Hanifa (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2020)
Roselle flower (Hibiscus sabdarifa L.) is one of the medicinal plants which is often used as traditional medicine. Roselle flower (Hibiscus sabdarifa L.) contains phenolic compounds such as tannins, saponins and flavonoids that are as antibacterial. Roselle flower (Hibiscus sabdarifa L.) can be made as a kombucha tea. Kombucha ia useful as an antibacterial, anticancer, improves liver function, anticholesterol, detoxification, improves the digestive system and maintains stamina. The purpose of this research were to find out the effect of kombucha roselle (Hibiscus sabdarifa L.) fermentation time against antibacterial activity of Escherichia coli. Kombucha roselle made by fermenting roselle stew, starter 10% and sugar 10% for 1 day, 3 days, 5 days, 7 days, 9 days, 11 days, 13 days and 15 days. Then, testing the effectiveness of antibacterial by method Cup-plate technique. The results showed that fermentation of kombucha rosella was able to inhibit the growth of Escherichia coli bacteria with different results according to the length of fermentation time. The results of data analysis using spearman test showed the fermentation time were take effect on e.coli antibacterial activity and continued with Mann Whitney test showed the fermentation of kombucha roselle has a significant inhibitory effect on bacterial growth. The most optimum inhibitory zone in inhibiting Escherichia coli is 15 days fermentation of kombucha roselle for 21,5 mm wich is categorized as very strong antibacterial activity.